TO COMPARE THE EFFECTIVENESS OF CRYOTHERAPY VERSUSTRANSCUTANEOUS ELECTRIC NERVE STIMULATION IN THEMANAGEMENT OF KNEE OSTEOARTHRITIS - Asim Ahmed et al (Baqai Journal of Health Sciences, 2024)
To compare the effectiveness of Cryotherapy therapy and Transcutaneous Electric Nerve Stimulation in the Management of knee osteoarthritis. This Quasi experimental study was carried out at Institute of Physical Medicine and Rehabilitation Dow University of Health Sciences Karachi. Total 60 Individuals with complain of painful knee osteoarthritis fulfilling inclusion criteria were selected on voluntarily basis. Selected patients were evenly divided and randomly allocated into two groups with age and gender matching. The group (A) received Cryotherapy along with exercises and (B) Group received a high frequency stimulation of TENS along with exercises. Individuals were treated four days per week for five consecutive weeks. Outcome was analyzed in both groups, on initialÊsession and on last session using Numeric pain rating Scale. The results of this study shows that both interventions helped in reduction of pain. On numeric pain rating scale lesser values were for cryotherapy as compare to that of TENS. The results it is suggest that cryotherapy is more effective than use of TENS and also the use of ice in Cryotherapy is much more cost effective procedure as compared to TENS